Composite solution and preparation method thereof, and electroluminescent device
By using electron transport materials, linear polymers and solvents in the composite solution, the stability and uniformity of the electron transport layer in the solution film formation technology are solved, and the performance and life of the light emitting device are improved.
Patent Information
- Application Number
- CN202111611650.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-27
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-12-27
AI Technical Summary
In solution film formation technology, the poor stability of the electron transport layer and the poor uniformity of the film layer lead to the impact of the surface morphology and luminous efficiency of the luminescent layer.
The composite solution is used to contain electron transport materials, linear polymers and solvents. The electron transport layer is prepared by inkjet printing technology, and the linear polymer is used to improve carrier transport capabilities and stability and reduce damage to the luminescent layer.
The stability of the electron transport layer and the uniformity of the film layer are improved, the life of the light emitting device is extended, and the luminous efficiency is improved.
Smart Images

Figure CN116355460B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of optoelectronic technology, and in particular to a composite solution and a preparation method thereof, and an electroluminescent device. Background Art
[0002] Electroluminescent devices, such as organic light-emitting diodes (OLED), are one of the most promising display technologies, with a series of outstanding advantages such as self-luminescence, high contrast, wide color gamut, large viewing angle, fast response speed, and flexible display. Most of the commercialized display products on the market are obtained through vacuum evaporation technology, while solution film forming technology (such as spin coating, inkjet printing, etc.) has lower production costs and simpler process flow than traditional vacuum evaporation technology, so it has received widespread attention in recent years.
[0003] With the continuous advancement of technology, many breakthroughs have been made in the research and development of solutions or inks corresponding to various organic layer materials. For example, inkjet printing hole injection layer (HIL) ink, hole transport layer ink (HTL) ink and red, green and blue corresponding light-emitting layer (EML) ink and other ink systems are relatively mature, and the life and efficiency of the products are guaranteed. The performance of devices prepared by solution film forming technology is gradually catching up with the performance of devices prepared by vacuum evaporation technology.
[0004] However, there are some problems with the current solution film forming technology. One of them is that the stability of the electron transport layer (ETL) prepared by solution film forming is not excellent. For example, when preparing other organic film layers (such as light-emitting layers) on the surface of the electron transport layer, the electron transport layer is easily destroyed by the solution of other organic film layers. Moreover, when the composite solution film is formed by inkjet printing technology, the composite solution will also cause the film thickness at the edge of the film layer to be greater than the film thickness in the middle during the curing film forming process due to the coffee ring effect, resulting in poor film uniformity.
[0005] In addition, when the light-emitting device is a device of an upright structure, in the process of preparing the electron transport layer based on the light-emitting layer using solution film-forming technology, the electron transport layer ink may also dissolve the material of the light-emitting layer or react with the material of the light-emitting layer, thereby destroying the formed light-emitting layer, resulting in adverse effects on the surface morphology, luminous efficiency, etc. of the prepared light-emitting layer. Summary of the invention
[0006] The embodiment of the present application provides a composite solution, and the electron transport layer prepared by the composite solution has excellent stability and good film uniformity.
[0007] The embodiments of the present application also provide a method for preparing the composite solution and an electroluminescent device.
[0008] The present application embodiment provides a composite solution, comprising: in terms of mass percentage,
[0009] Electron transport materials 0.1% to 25%;
[0010] Linear polymers 1% to 20%; and
[0011] Solvent 55%~98%.
[0012] Optionally, in some embodiments of the present application, the viscosity of the composite solution is 1 to 20 cps; and / or
[0013] The surface tension of the composite solution is 20-40 dyne / cm.
[0014] Optionally, in some embodiments of the present application, the electron transport material is selected from one or more of alcohol-soluble organic small molecule compounds, alcohol-soluble conjugated polyelectrolytes, and inorganic nanoparticles.
[0015] Optionally, in some embodiments of the present application, the linear polymer is selected from one or more of polyethyleneimine, polyethylene glycol, polyacrylamide, partially hydrolyzed polyacrylamide, and polyvinylpyrrolidone.
[0016] Optionally, in some embodiments of the present application, the solvent is an alcohol solvent.
[0017] Optionally, in some embodiments of the present application, the composite solution further includes a surfactant, and the surfactant is 0.1% to 10% by mass.
[0018] Optionally, in some embodiments of the present application, the surfactant is selected from one or more of imidazole and its derivatives, phenol, and hydroquinone.
[0019] In addition, a method for preparing a composite solution comprises:
[0020] Providing raw materials, the raw materials include electron transport material, linear polymer and solvent, in which, by mass percentage, the electron transport material is 0.1% to 25%, the linear polymer is 1% to 20% and the solvent is 55% to 98%;
[0021] The raw materials are mixed to obtain a multi-component mixture, and the multi-component mixture is heated until it becomes clear.
[0022] In addition, a method for preparing a composite solution comprises:
[0023] Providing a solute and a solvent, wherein the solute comprises an electron transport material and a linear polymer, and the solvent is divided into a plurality of unit solvents, wherein the number of unit solvents corresponds to the number of solute categories; in terms of mass percentage, the electron transport material comprises 0.1% to 25%, the linear polymer comprises 1% to 20%, and the solvent comprises 55% to 98%;
[0024] Mixing each type of solute with multiple units of solvents to obtain multiple binary mixtures, and heating the multiple binary mixtures until they are clear; and
[0025] Mix multiple binary mixtures.
[0026] In addition, an electroluminescent device includes an electron transport layer, wherein the electron transport layer is prepared by the composite solution.
[0027] Compared with the prior art, the composite solution provided by the present invention introduces a linear polymer, which cooperates with the electron transport material and the solvent to complement each other. When the formed solution is used to prepare the electron transport layer, it can change the electron transport capacity of the prepared electron transport layer, balance the carrier transport, and improve the device efficiency; and the stability of the electron transport layer prepared by the composite solution is also excellent. When the composite solution is used in inkjet printing technology, the prepared electron transport layer also has good film uniformity. In addition, the composite solution can improve or even avoid damage to the light-emitting layer, reduce or even avoid adverse effects on the surface morphology, luminous efficiency, etc. of the light-emitting layer, thereby improving the performance of the light-emitting device and extending the life of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 is a schematic structural diagram of a substrate provided with an anode;
[0030] Figure 2 is a schematic structural diagram of the electroluminescent device provided in Example 1 of the present application;
[0031] Figure 3 It is the JV curve obtained by the test.
[0032] Wherein, the accompanying drawings are described as follows:
[0033] Substrate 10; base substrate 101; TFT layer 102; planar layer 103; pixel definition layer 104; pixel region 105; anode 201; hole injection layer 202; hole transport layer 203; light emitting layer 204; electron transport layer 205; electron injection layer 206; cathode 207. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of this application.
[0035] The embodiments of the present application provide a composite solution and a preparation method thereof, and an electroluminescent device. The following are detailed descriptions. It should be noted that the description order of the following embodiments does not limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0036] The embodiment of the present application provides a composite solution, comprising: in terms of mass percentage, 0.1% to 25% of an electron transport material; 1% to 20% of a linear polymer; and 55% to 98% of a solvent.
[0037] The composite solution with the above ratio has suitable viscosity and surface tension, which is conducive to solution film formation; and based on the above components and dosage ratios, the obtained ETL solution can also meet the electron transport efficiency requirements of the electron transport layer to be prepared. Taking the use of the above composite solution in inkjet printing technology as an example, when the mass percentage of each component in the composite solution is within the above corresponding range, the electron transport efficiency of the prepared electron transport layer can meet the working requirements of the device.
[0038] In some embodiments, the viscosity of the composite solution is 1-20 cps; and / or
[0039] The surface tension of the composite solution is 20-40 dyne / cm. Taking the use of the composite solution in inkjet printing technology as an example, when the viscosity and surface tension of the composite solution are within the above range, the requirements of the inkjet printing process can be well met.
[0040] In the composite solution, the electron transport material can be selected from one or more of alcohol-soluble organic small molecule compounds, alcohol-soluble conjugated polyelectrolytes, and inorganic nanoparticles. Among them, the small molecule compound refers to a compound with a molecular weight not exceeding 1000, which can be 2,7-bis(diphenylphosphinyl)-9,9'-spirobi[fluorene], 1,3,5-tris(diphenylphosphinyl-phenyl-3-yl)benzene or other alcohol-soluble organic small molecule compounds commonly used in the art that can be used as electron transport materials. The alcohol-soluble conjugated polyelectrolyte can be selected from poly[9,9-dioctylfluorene-9,9-bis(N,N-dimethylaminopropyl)fluorene], 9,9-bis[3'-(N,N-dimethylamino)propyl-2,7-fluorene]-alternate-2,7-(9,9-dioctylfluorene), 4,7-diphenyl-1,10-phenanthroline, 1,3,5-tri(3-pyridin-3-yl-phenyl)benzene, diphenylphosphine oxide derivatives or other alcohol-soluble conjugated polyelectrolytes commonly used in the art that can be used as electron transport materials. The inorganic nanoparticles can be selected from zinc oxide nanoparticles.
[0041] The linear polymer in the composite solution of the present invention is preferably a linear polymer that also serves as a non-ionic surfactant. In this way, the linear polymer has the properties of a non-ionic surfactant—it does not exist in an ionic state in the solution and has high stability. The addition of the linear polymer as a non-ionic surfactant can also reduce the surface tension and surface free energy of the composite solution and improve the spreadability of the composite solution. Compared with the same volume solution (ink) that does not contain a linear polymer such as polyethyleneimine, the solution containing the linear polymer has a larger spreading area and is more conducive to solution film formation. In addition, when the composite solution is used on other film layers, the linear polymer in the solution is first deposited on the aforementioned "other film layers" to complete the film layer contact and fix the film layer structure, thereby reducing the damage of the composite solution to other film layers. Furthermore, since the conduction band energy level of the linear polymer itself in the composite solution is greatly different from the conduction band energy level of the electron transport material, the electron transport capacity of the above-mentioned composite solution after film formation will change due to the addition of the linear polymer.
[0042] The linear polymer can be selected from one or more of polyethyleneimine (PEI), polyethylene glycol (PEG), polyacrylicamide (PAM), partially hydrolyzed polyacrylamide (HPAM), and polyvinyl pyrrolidone (PVP). The linear polymer is preferably PEI, which is also called polyaziridine. It is a water-soluble polymer that is soluble in water and ethanol but insoluble in benzene. The long molecular chain of PEI can improve the film structure, ensure the uniformity of the electron transport layer film formation, and also give the electron transport layer excellent stability.
[0043] The solvent in the composite solution of the present invention can be a polar solvent or a non-polar solvent, preferably a polar solvent. When the solution film forming method is used to prepare the electron transport layer on the organic film layer (such as the light-emitting layer), the polar solvent in the composite solution has a relatively weak degree of solubility of the light-emitting layer material and a relatively weak degree of chemical reaction with the light-emitting layer material, and has less damage to the light-emitting layer, and the prepared device has a higher luminous efficiency and a longer service life.
[0044] Furthermore, the polar solvent is preferably an alcohol solvent. Alcohol solvents have weak solubility for most light-emitting layer materials, which can reduce or even avoid damage to the light-emitting layer. The alcohol solvent can be a mixture of one alcohol compound or multiple alcohol compounds. For example, in some embodiments, the alcohol solvent is a mixture of two monohydric alcohols, and the above alcohol compound can be a monohydric alcohol or a polyhydric alcohol. The alcohol solvent is preferably a mixture of butanol and ethylene glycol, wherein the mass ratio of butanol to ethylene glycol can be 1:2 to 4, and the preferred mass ratio is 1:3.
[0045] In some embodiments, the composite solution may further include a surfactant, and the surfactant is 0.1% to 10% by mass. When the surface energy of the composite solution obtained by only mixing the electron transport layer material, the linear polymer and the solvent is large and it is difficult to meet the requirements of the solution film forming industry, a surfactant may be added. After the surfactant is added, the surface tension of the composite solution is further reduced and the spreadability is further improved. The surfactant in the composite solution of the present invention can be one or more of imidazole and its derivatives, phenol, and hydroquinone.
[0046] The present application also provides two methods for preparing the composite solution.
[0047] Method 1 includes:
[0048] Providing raw materials, the raw materials include electron transport material, linear polymer and solvent, in which, by mass percentage, the electron transport material is 0.1% to 25%, the linear polymer is 1% to 20% and the solvent is 55% to 98%;
[0049] The raw materials are mixed to obtain a multi-component mixture, and the multi-component mixture is heated until it becomes clear.
[0050] In method one, mixing can be performed by stirring, ultrasound, etc., and of course other mixing methods can also be used; the heating in method one is to make the electron transport material and linear polymer in the composite solution better dissolved in the solvent, and the heating temperature is generally 80-100°C, and the maximum is not higher than 150°C; the heating time should be adjusted according to the selected solvent, solute type and amount, and the heating can be stopped when the mixture is clear and transparent and the solute is completely dissolved.
[0051] Furthermore, method one may include: adding an electron transport material to a solvent to form a first mixture, heating and stirring the first mixture until the first mixture is clarified, then adding a certain amount of a linear polymer to the first mixture to form a second mixture, and heating the second mixture until it is clarified.
[0052] If the feedstock also includes a surfactant, the surfactant can be added to the clarified second mixture.
[0053] Method 2 includes:
[0054] Providing a solute and a solvent, wherein the solute comprises an electron transport material and a linear polymer, and the solvent is divided into a plurality of unit solvents, wherein the number of unit solvents corresponds to the number of solute categories; in terms of mass percentage, the electron transport material comprises 0.1% to 25%, the linear polymer comprises 1% to 20%, and the solvent comprises 55% to 98%;
[0055] Mixing each type of solute with multiple units of solvents to obtain multiple binary mixtures, and heating the multiple binary mixtures until they are clear; and
[0056] Mix multiple binary mixtures.
[0057] The method and purpose of mixing and heating in Method 2 are consistent with those in Method 1, and will not be repeated here. The "divided into" in Method 2 mainly means that the solvent is divided into multiple units of solvent, and is not limited to specific operation actions; the volumes of the multiple units of solvent divided can be the same or different, and can be determined according to the substances that need to be dissolved; "corresponding" means that the number of units of solvent divided is the same as the number of solute categories, and mixing each type of solute with multiple units of solvent means mixing one solute with one unit of solvent. For example, if the solute includes two types of electron transport materials and linear polymers, the number of unit solvents is two, and two units of solvent are mixed with electron transport materials and linear polymers respectively. Compared with Method 1, Method 2 is easier to control the proportion of each component.
[0058] The embodiment of the present application further provides an electroluminescent device, comprising an electron transport layer (ETL), wherein the electron transport layer is prepared by the above-mentioned composite solution.
[0059] The electroluminescent device also includes a cathode, an anode, a light-emitting layer (EML), and may also include other functional layers (such as a hole injection layer (HIL), a hole transport layer (HTL)). The materials of the cathode, anode, light-emitting layer and other functional layers can be selected from the corresponding materials commonly used in the art, such as the material of the anode can be indium tin oxide (ITO), fluorine-doped tin oxide (FTO), indium zinc oxide (IZO), etc., and the cathode material can be silver (Ag), aluminum (Al), gold (Au), etc. The electroluminescent device provided in the embodiment of the present application can be a positive structure electroluminescent device or an inverted structure electroluminescent device; according to the direction of the emitted light, the electroluminescent device provided in the present application can be any one of a top emitter device, a bottom emitter device, and a double-sided emission device. The light-emitting layer in the electroluminescent device provided by the present invention may include one or more of the red, green, and blue light-emitting layers. The electron transport layer in the electroluminescent device can be made by inkjet printing, spin coating, or other techniques well known in the art using the composite solution provided by the present invention.
[0060] The electroluminescent device provided by the present invention can be prepared by the following method:
[0061] Step 1: Provide a substrate 10. The structure of the substrate 10 is shown in Figure 1 The substrate 10 includes a base substrate 101, a TFT layer 102, a planar layer 103, and a pixel definition layer 104. The recessed area in the figure is a pixel area 105, which can be used to form an electrode, an ETL, a light-emitting layer, etc. The figure exemplarily shows an anode located on the planar layer 103 and formed in the pixel area 105.
[0062] Step 2: Prepare the hole injection layer, hole transport layer and light emitting layer on the anode in sequence by inkjet printing. After preparing the three layers of OLED organic functional layers, each layer can be dried or vacuum dried as required to form a dense and stable organic film layer.
[0063] Step 3: Add the electron transport layer ink provided by the present invention to the inkjet printing device, adjust the printing speed and inkjet droplet size, and then print a specific number of droplets corresponding to the required electron transport film thickness evenly and stably to the pixel area. Then, dry the liquid film layer under negative pressure, and further dry the film layer at high temperature after the film layer is solidified to ensure the formation of a stable, dry and dense electron transport film layer.
[0064] Step 4: Place the printed semi-finished device into a vacuum evaporation chamber, and under high vacuum conditions, deposit an electron injection layer (EIL) and a cathode in sequence onto the semi-finished device to form a complete electroluminescent device structure.
[0065] Example 1
[0066] This embodiment provides a composite solution, which comprises, by mass percentage:
[0067] 1,3,5-Tris(diphenylphosphoryl-phenyl-3-yl)benzene 0.5%;
[0068] Polyacrylamide 8.5%;
[0069] Alcohol solvent 91%;
[0070] The alcohol solvent in this embodiment is ethylene glycol.
[0071] Example 2
[0072] This embodiment provides a composite solution, which comprises, by mass percentage:
[0073]
[0074] The alcohol solvent in this embodiment is a mixture of butanol and ethylene glycol, wherein the mass ratio of butanol to ethylene glycol is 1: 3. According to the test, the viscosity of the composite solution in this embodiment is 9 cps, and the surface tension is 35 dyne / cm.
[0075] This embodiment also provides a method for preparing the composite solution, comprising:
[0076] Providing 2,7-bis(diphenylphosphinyl)-9,9'-spirobis[fluorene], polyethyleneimine, hydroquinone, butanol and ethylene glycol in the above mass ratio;
[0077] Butanol and ethylene glycol are mixed to form an alcohol solvent in the composite solution, and the above-mentioned 2,7-bis(diphenylphosphinyl)-9,9'-spirobis[fluorene] is added to the alcohol solvent, heated and stirred at 85°C, and a transparent clear solution is formed after the solvent dissolves all the 2,7-bis(diphenylphosphinyl)-9,9'-spirobis[fluorene]. Subsequently, the above-mentioned polyethyleneimine is added to the above-mentioned transparent clear solution, and heating and stirring at 85°C are continued to form a clear transparent solution, and then a surfactant hydroquinone is added to obtain a composite solution.
[0078] In addition, this embodiment also provides an electroluminescent device, including: a substrate, an anode, a hole injection layer (HIL), a hole transport layer (HTL), a light-emitting layer (EML), an electron transport layer (ETL) and a cathode; wherein the HIL, HTL, EML and ETL can be prepared by inkjet printing technology, the ETL is prepared by the above composite solution, and the cathode is prepared by evaporation after the ETL is cured into a film. The organic electroluminescent device prepared in this embodiment is a green light device.
[0079] Example 3
[0080] This embodiment provides a composite solution (Aq2), which comprises, in terms of mass percentage:
[0081]
[0082]
[0083] The alcohol solvent in this embodiment is a mixture of butanol and ethylene glycol, wherein the mass ratio of butanol to ethylene glycol is 1:3.
[0084] This embodiment also provides a method for preparing the composite solution, comprising:
[0085] Providing 1,3,5-tris(diphenylphosphoryl-phenyl-3-yl)benzene; polyethyleneimine; hydroquinone; butanol and ethylene glycol in the above mass ratio;
[0086] Butanol and ethylene glycol are mixed to form the solvent in the composite solution, and the mixed solvent is divided into three parts, and the volume ratio of the three solvents is 1:6:1; the above-mentioned 1,3,5-tris(diphenylphosphoryl-phenyl-3-yl)benzene is mixed with one of the above-mentioned solvents with a volume ratio of 1, the above-mentioned polyethyleneimine is mixed with the above-mentioned solvent with a volume ratio of 6, and the above-mentioned hydroquinone is mixed with the above-mentioned other solvent with a volume ratio of 1 to form three binary mixtures; the above-mentioned three binary mixtures are heated at 85°C until clear and transparent, and the above-mentioned three binary mixtures are mixed, and the composite solution is obtained after shaking evenly. After testing, the viscosity of the composite solution in this embodiment is 11cps and the surface tension is 22.8dyne / cm.
[0087] In addition, if Figure 2 As shown, an organic electroluminescent device (device 2) is provided, including: a substrate 10, an anode 201, a hole injection layer (HIL) 202, a hole transport layer (HTL) 203, a light-emitting layer (EML) 204, an electron transport layer (ETL) 205, an electron injection layer (EIL) 206 and a cathode 207; wherein, HIL202, HTL203, EML204, and ETL205 can be prepared by inkjet printing technology, ETL205 is prepared by the above-mentioned composite solution, and the cathode is prepared by evaporation after ETL205 is cured into a film. In the device, the film thickness of HIL202 is 100nm, the film thickness of HTL203 is 100nm, the film thickness of EML204 is 65nm, the film thickness of ETL205 is 25nm, the film thickness of EIL206 is 1nm, and the film thickness of cathode 207 is 22nm. The organic electroluminescent device prepared in this embodiment is a red light device.
[0088] Example 4
[0089] This embodiment provides a composite solution (Aq3). Compared with Example 3, the composite solution only has the mass percentage of polyethyleneimine changed to 10% and the mass percentage of the alcohol solvent changed to 86.5%. The other components and amounts are unchanged. The composition and ratio of the alcohol solvent are also unchanged. A mixture of butanol and ethylene glycol with a mass ratio of 1:3 is still selected. After testing, the viscosity of the composite solution in this embodiment is 13.65cps and the surface tension is 23dyne / cm.
[0090] This embodiment also provides an organic electroluminescent device (device three) prepared using the above composite solution. The device structure, preparation method, and film thickness of the organic electroluminescent device are the same as those of the organic electroluminescent device in Example 3. That is, compared with Example 3, this embodiment is different only in the ETL solution used to prepare the organic electroluminescent device.
[0091] Example 5
[0092] This embodiment provides a composite solution (Aq4). Compared with Example 3, the composite solution only has the mass percentage of polyethyleneimine changed to 20% and the mass percentage of the alcohol solvent changed to 76.5%. The other components and amounts are unchanged. The composition and ratio of the alcohol solvent are also unchanged, and a mixture of butanol and ethylene glycol with a mass ratio of 1:3 is still selected. After testing, the viscosity of the composite solution in this embodiment is 14.17cps and the surface tension is 23.5dyne / cm.
[0093] This embodiment also provides an organic electroluminescent device (device four) prepared using the above composite solution. The device structure, preparation method, and film thickness of the organic electroluminescent device are the same as those of the organic electroluminescent device in Example 3. That is, compared with Example 3, this embodiment is different only in the ETL solution used to prepare the organic electroluminescent device.
[0094] Comparative Example 1
[0095] This comparative example provides a composite solution (Aq1). Compared with Example 3, the composite solution only has the mass percentage of polyethyleneimine changed to 0% and the mass percentage of the alcohol solvent changed to 96.5%. The other components and amounts are unchanged. The composition and ratio of the alcohol solvent are also unchanged, and a mixture of butanol and ethylene glycol with a mass ratio of 1:3 is still selected. After testing, the viscosity of the composite solution in this example is 10.5cps and the surface tension is 21.9dyne / cm.
[0096] This reference example also provides an organic electroluminescent device (device 1) prepared using the above-mentioned composite solution. The device structure, preparation method, and film thickness of the organic electroluminescent device are the same as those of the organic electroluminescent device in Example 3. That is, compared with Example 3, only the ETL solution used to prepare the organic electroluminescent device is different in this reference example.
[0097] Comparative Example 2
[0098] This comparative example provides a composite solution (Aq5). Compared with Example 3, the composite solution only has the mass percentage of polyethyleneimine changed to 30% and the mass percentage of the alcohol solvent changed to 66.5%. The other components and amounts are unchanged. The composition and ratio of the alcohol solvent are also unchanged, and a mixture of butanol and ethylene glycol with a mass ratio of 1:3 is still selected. After testing, the viscosity of the composite solution in this example is 18.53cps and the surface tension is 30.2dyne / cm.
[0099] This reference example also provides an organic electroluminescent device (device five) prepared using the above-mentioned composite solution. The device structure, preparation method, and film thickness of the organic electroluminescent device are the same as those of the organic electroluminescent device in Example 3. That is, compared with Example 3, only the ETL solution used to prepare the organic electroluminescent device is different in this reference example.
[0100] Comparative Example 3
[0101] This comparative example provides a composite solution (Aq6). Compared with Example 3, the mass percentage of polyethyleneimine in the composite solution is changed to 50%, and the mass percentage of the alcohol solvent is changed to 46.5%. The other components and amounts are unchanged. The composition and ratio of the alcohol solvent are also unchanged, and a mixture of butanol and ethylene glycol with a mass ratio of 1:3 is still selected. After testing, the viscosity of the composite solution in this example is 20.01cps and the surface tension is 35.2dyne / cm.
[0102] This reference example also provides an organic electroluminescent device (device six) prepared using the above composite solution. The device structure, preparation method, and film thickness of the organic electroluminescent device are the same as those of the organic electroluminescent device in Example 3. That is, compared with Example 3, only the ETL solution used to prepare the organic electroluminescent device is different in this reference example.
[0103] The optical and electrical performance tests were conducted on the organic electroluminescent devices prepared in Example 3-Comparative Example 3. The test results are shown in Table 1. Wherein, J10 indicates that the organic electroluminescent device has a current density of 10 mA / cm 2 CIEx and CIEy represent the x-axis and y-axis of the color coordinates respectively, and LT@1000nit represents the time taken for the brightness to decay to 95% of the initial brightness at 1000nit.
[0104] Table 1 Test data of optical and electrical properties of organic electroluminescent devices
[0105]
[0106]
[0107] From Table 1 we can see that:
[0108] 1. As the proportion of PEI increases, the corresponding organic electroluminescent device reaches a current density of 10mA / cm 2 The voltage required for (J10) increases, and when the PEI content in the composite solution is less than 20%, the increase in J10 voltage is not obvious, but when the PEI content in the composite solution is 30% (device five) and 50% (device six), the J10 voltage increases significantly. This shows that when the PEI content in the composite solution exceeds 20%, the transmission capacity of the electron transport layer decreases significantly. The voltage when the brightness of devices one to six reaches 1000nit has the same change trend as the J10 voltage of devices one to six;
[0109] 2. The test results show that in devices 1 to 4, as the proportion of PEI in the electron transport layer increases, the efficiency CE of the organic electroluminescent device does not change significantly, but when the content of PEI in the composite solution exceeds 20%, the efficiency CE of the organic electroluminescent device decreases significantly, which also proves that when the PEI content in the composite solution exceeds 20%, the transmission capacity of the electron transport layer decreases significantly;
[0110] 3. In devices 1 to 4, as the proportion of PEI in the electron transport layer increases, the device life will gradually increase. After calculation, the life of device 4 is 30% longer than that of device 1. This shows that with the addition of PEI, the stability of the ETL layer is enhanced; but when the content of PEI in the composite solution exceeds 20%, the device life is greatly reduced due to the excessive impact of PEI on the electron transport layer.
[0111] In addition, in order to determine the electron transport capacity of the electron transport layer prepared from the composite solution with different PEI contents, the above Aq1 to 6 were used to prepare single-carrier devices, and the structure of the single-carrier device was IZO (40 nm) / electron transport layer (30 nm) / evaporated Al (100 nm). The prepared single-carrier devices were numbered as single-carrier device 1 (corresponding to Aq1), single-carrier device 2 (corresponding to Aq2), single-carrier device 3 (corresponding to Aq3), single-carrier device 4 (corresponding to Aq4), single-carrier device 5 (corresponding to Aq5) and single-carrier device 6 (corresponding to Aq6), and the JV curves of each single-carrier device were tested. The results are shown in FIG. Figure 3 Among them, curves af are JV curves of single carrier devices 1-6 respectively.
[0112] pass Figure 3 It can be seen that when the PEI content in the composite solution exceeds 20%, the current density of the single-carrier device at the same voltage is significantly reduced, which indicates that the electron transport capacity of the electron transport layer is greatly reduced. Therefore, it is more appropriate to keep the PEI content in the composite solution below 20%.
[0113] In addition, in order to compare the spreadability of the composite solutions provided in the examples and the control examples, a spreadability experiment was conducted using Aq1 in control example 1 and Aq2 in example 2. The experiment showed that when the same volume of Aq1 and Aq2 were printed on the same luminescent layer, the spread area of Aq2 was larger, indicating that the ink provided in the examples had better spreadability.
[0114] The above is a detailed introduction to a composite solution and a preparation method thereof, and an organic electroluminescent device provided in the embodiments of the present application. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technicians in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A composite solution, characterized in that: include: In terms of mass percentage, Electron transport materials 0.1% to 25%; Linear polymer 10% to 20%; Solvent 55%~98%; as well as Hydroquinone 0.1%~10%; The linear polymer is selected from polyethylene imine; The solvent is a polar solvent; The electron transport material is selected from one or more of alcohol-soluble organic small molecule compounds and alcohol-soluble conjugated polyelectrolytes, wherein the small molecule compound refers to a compound with a molecular weight not exceeding 1000.
2. The composite solution according to claim 1, characterized in that: The viscosity of the composite solution is 1 to 20 cps; and / or The surface tension of the composite solution is 20-40 dyne / cm.
3. The composite solution according to claim 1, characterized in that: The polar solvent is an alcohol solvent.
4. A method for preparing a composite solution according to any one of claims 1 to 3, characterized in that: include: Providing raw materials, the raw materials include electron transport material, linear polymer, hydroquinone and solvent, in which, by mass percentage, the electron transport material is 0.1% to 25%, the linear polymer is 10% to 20%, the hydroquinone is 0.1% to 10% and the solvent is 55% to 98%; the linear polymer is selected from polyethyleneimine, and the solvent is a polar solvent; the electron transport material is selected from one or more of alcohol-soluble organic small molecule compounds and alcohol-soluble conjugated polyelectrolytes, wherein the small molecule compound refers to a compound with a molecular weight not exceeding 1000; The raw materials are mixed to obtain a multi-component mixture, and the multi-component mixture is heated until it becomes clear.
5. A method for preparing a composite solution according to any one of claims 1 to 3, characterized in that: include: A solute and a solvent are provided, wherein the solute comprises an electron transport material, hydroquinone and a linear polymer, the solvent is divided into a plurality of unit solvents, and the number of the unit solvents corresponds to the number of categories of the solute; in terms of mass percentage, the electron transport material is 0.1% to 25%, the linear polymer is 10% to 20%, the hydroquinone is 0.1% to 10% and the solvent is 55% to 98%; the linear polymer is selected from polyethyleneimine, and the solvent is a polar solvent; the electron transport material is selected from one or more of an alcohol-soluble organic small molecule compound and an alcohol-soluble conjugated polyelectrolyte, wherein the small molecule compound refers to a compound with a molecular weight not exceeding 1000; Mixing each type of the solute with a plurality of the unit solvents to obtain a plurality of binary mixtures, and heating the plurality of the binary mixtures until they are clear; as well as Multiple portions of the binary mixture are mixed.
6. A light emitting device, characterized in that: It comprises an electron transport layer, and the electron transport layer is prepared by the composite solution according to any one of claims 1 to 3.
Citation Information
Patent Citations
Inverted quantum dot light emitting diode containing composite electron transport layer
KR102239351B1